Recombinant antigens from Phlebotomus perniciosus saliva as markers of canine exposure to visceral leishmaniases vector - Drahota, Jan; Martin-Martin, Ines; Sumova, Petra; Rohousova, Iva; Jimenez, Maribel; Molina, Ricardo; Volf, Petr (PLoS neglected tropical diseases, 2014)
BACKGROUND: Phlebotomus perniciosus is the main vector in the western Mediterranean area of the protozoan parasite Leishmania infantum, the causative agent of canine and human visceral leishmaniases. Infected dogs serve as a reservoir of the disease, and therefore measuring the exposure of dogs to sand fly bites is important for estimating the risk of L. infantum transmission. In bitten hosts, sand fly saliva elicits a specific antibody response that reflects the intensity of sand fly exposure. As screening of specific anti-saliva antibodies is limited by the availability of salivary gland homogenates, utilization of recombinant salivary proteins is a promising alternative. In this manuscript we show for the first time the use of recombinant salivary proteins as a functional tool for detecting P. perniciosus bites in dogs. METHODOLOGY/PRINCIPAL FINDINGS: The reactivity of six bacterially-expressed recombinant salivary proteins of P. perniciosus, yellow-related protein rSP03B, apyrases rSP01B and rSP01, antigen 5-related rSP07, ParSP25-like protein rSP08 and D7-related protein rSP04, were tested with sera of mice and dogs experimentally bitten by this sand fly using immunoblots and ELISA. In the immunoblots, both mice and canine sera gave positive reactions with yellow-related protein, both apyrases and ParSP25-like protein. A similar reaction for recombinant salivary proteins was observed by ELISA, with the reactivity of yellow-related protein and apyrases significantly correlated with the antibody response of mice and dogs against the whole salivary gland homogenate. CONCLUSIONS/SIGNIFICANCE: Three recombinant salivary antigens of P. perniciosus, yellow-related protein rSP03B and the apyrases rSP01B and rSP01, were identified as the best candidates for evaluating the exposure of mice and dogs to P. perniciosus bites. Utilization of these proteins, or their combination, would be beneficial for screening canine sera in endemic areas of visceral leishmaniases for vector exposure and for estimating the risk of L. infantum transmission in dogs.
Keywords: Molecular Sequence Data; Sequence Analysis, DNA; Antibodies; psi; protilátky; imunoblotting; rekombinantní proteiny; Dogs; Mice; Phlebotomus; slinné proteiny a peptidy; Salivary Proteins and Peptides; Immunoblotting; ženské pohlaví; ELISA; zvířata; Humans; hmyzí proteiny; Insect Bites and Stings; kousnutí a bodnutí hmyzem; sekvenční analýza DNA; myši; molekulární sekvence - údaje; Enzyme-Linked Immunosorbent Assay; Female; Insect Proteins; lidé; Recombinant Proteins; Animals